High fusion performance at high Ti/Te in JET-ILW baseline plasmas with high NBI heating power and low gas puffing. (1st February 2018) - Kim, Hyun-Tae; Sips, A.C.C.; Romanelli, M.; Challis, C.D.; Rimini, F.; Garzotti, L.; Lerche, E.; Buchanan, J.; Yuan, X.; Kaye, S.
Abstract: This paper presents the transport analysis of high density baseline discharges in the 2016 experimental campaign of the Joint European Torus with the ITER-Like Wall (JET-ILW), where a significant increase in the deuterium–deuterium (D–D) fusion neutron rate ( 2.8 × 10 16 s −1 ) was achieved with stable high neutral beam injection (NBI) powers of up to 28 MW and low gas puffing. Increase in T i exceeding T e were produced for the first time in baseline discharges despite the high electron density; this enabled a significant increase in the thermal fusion reaction rate. As a result, the new achieved record in fusion performance was much higher than the previous record in the same heating power baseline discharges, where T i = T e . In addition to the decreases in collisionality and the increases in ion heating fraction in the discharges with high NBI power, T i > T e can also be attributed to positive feedback between the high T i / T e ratio and stabilisation of the turbulent heat flux resulting from the ion temperature gradient driven mode. The high T i / T e ratio was correlated with high rotation frequency. Among the discharges with identical beam heating power, higher rotation frequencies were observed when particle fuelling was provided by low gas puffing and pellet injection. This reveals that particle fuelling played a key role for achieving high T i / T e, and the improved fusion performance.